2020
DOI: 10.1177/2158244020969394
|View full text |Cite
|
Sign up to set email alerts
|

How Does Sustainable Leadership Influence Sustainable Performance? Empirical Evidence From Selected ASEAN Countries

Abstract: Presently, sustainable leadership has emerged as an effective leadership style to cope with sustainable challenges. Extent literature has recommended exploring the mechanism and conditional boundaries for the significant effect of sustainable leadership on sustainable performance. Therefore, this study would investigate the mediating mechanism of organizational learning and the psychological empowerment as conditional factor on the sustainable leadership–sustainable performance relationship. The cluster-sampli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
108
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 102 publications
(113 citation statements)
references
References 99 publications
(155 reference statements)
3
108
0
2
Order By: Relevance
“…In Singh et al (2020), product innovation mediated the green HRM practicesenvironmental performance relationship. Past research also offered scientific evidence concerning the mediating impact of psychological safety and organisational learning involving the sustainable leadership-sustainable performance relationship, hence amplifying the presence of psychological empowerment Iqbal et al, 2020a;. In a study involving Taiwanese organisations that manufactured hybrid vehicles, Huang and Li (2017) revealed that innovation mediated the market demand impact on economic performance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Singh et al (2020), product innovation mediated the green HRM practicesenvironmental performance relationship. Past research also offered scientific evidence concerning the mediating impact of psychological safety and organisational learning involving the sustainable leadership-sustainable performance relationship, hence amplifying the presence of psychological empowerment Iqbal et al, 2020a;. In a study involving Taiwanese organisations that manufactured hybrid vehicles, Huang and Li (2017) revealed that innovation mediated the market demand impact on economic performance.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, vision-sharing, experimentation empowerment and amicable leadership-employee relationship were highly sorted as essential qualities for organisational innovations (Elkins & Keller, 2003;Juhro & Aulia, 2019). In this regard, sustainable leadership reflects on offering a psychologically safe workplace for the staff (Iqbal et al, 2020a).…”
Section: The Mediating Role Of Frugal Innovationmentioning
confidence: 99%
“…Sustainable leaders also nurture generation and sharing of ideas, two-way communication, which leads to a mentally secure environment for innovation [33,36]. A polite relationship between top management and employees also plays a critical role in promoting creative activities within organizations [42], which is one of the fundamental practices of sustainable leadership [27]. By innovating incrementally, sustainable leadership practices introduce continuous improvements in products and processes at a small scale [43,44].…”
Section: The Environmental Innovation As Mediatormentioning
confidence: 99%
“…Considering the insufficiency of empirical evidence about the role of sustainable leadership and its relationship with environmental innovation [27,28], there are limited studies on the environmental performance of small and medium enterprises (SMEs) [3] and environmental challenges faced by the frontier Asia region. The present research fulfills the research gap by investigating the mediating effect of environmental innovation on the relationship of sustainable leadership with environmental performance and the conditional effect of managerial discretion.…”
Section: Introductionmentioning
confidence: 99%
“…One of the ways to achieve sustainable development is for business organisations to accept the challenges of sustainability as an opportunity and transform their business models accordingly. Sustainability is a new business trend that has fundamentally changed the demands placed on business leaders and has created a new type of leadership termed sustainable leadership (Virakul, 2015;Igbal et al, 2020).…”
Section: Introductionmentioning
confidence: 99%